Paraplegia Caused By Vertex Epidural Hematoma and Lumbal L1 Burst Compression Fracture: A Rare Case Report - I Putu Dhidhi Pradnya Suryadiarsa; I Putu Ananta Wijaya Sabudi; Janaari Pramana Putri Gelgel (Jurnal Ilmu Multidisiplin, 2025)
Paraplegia is most commonly caused by spinal cord trauma and is rarely the result of head injury. In this case report, we present a rare case of paraplegia caused by a vertex epidural hematoma (EDH) and L1 burst compression fracture. A 55-year-old female patient was diagnosed with vertex-parietal right EDH, right and left parietal subarachnoid hemorrhage (SAH), traumatic cerebral edema, open depressed comminuted fracture of the vertex, linear fracture of the right parietal bone, L1 compression fracture, and lower limb paraplegia. The patient underwent emergency debridement, craniotomy for EDH evacuation, reconstruction, and intracranial pressure (ICP) monitoring. One week after the craniotomy, L1 decompression and stabilization fusion were performed. The patient showed clinical improvement, received rehabilitation, and was discharged after 11 days of hospitalization. We conclude that paraplegia can be caused by vertex EDH and L1 compression fracture. Accurate diagnosis and appropriate management can lead to a favorable prognosis.